Mortality rate and risk factors for relaparotomy after caesarean section: a systematic review and meta-analysis - Dan Shan; Jinbiao Han; Xi Tan; Pingjing Yu; Yitong Cai; Ke Yi (BMC Pregnancy and Childbirth)
Abstract Background The high prevalence of caesarean section (CS) is a global concern. Relaparotomy is needed when conservative managements are not effective in CS complications. This study aimed to systematically review and meta-analyze the mortality rate and risk factors of relaparotomy after CS. Methods Based on a pre-registered protocol, we searched 11 databases. The MOOSE guideline was followed, and the reporting was in accordance with the PRISMA statement. A Freeman-Tukey double arcsine transformation was used to transform the raw data, and a random-effects meta-analytic model was applied. The quality of the evidence was evaluated by Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. Results The qualities of the pooled results were assessed to be “very low” based on the inclusion of observational studies. A total of 40 studies were retrieved. The mortality rate in patients after relaparotomy was 7.24% (95%CI 4.10-11.03%). Significant gap existed between high-resources and low-resources countries. In developed areas this rate was 0.56% and in places of low resources this rate was 16.90%. Higher CS rate correlated with higher mortality. Over 70% of the relaparotomies followed emergent CS. Risk factors associated with relaparotomy included higher maternal age, CS performed in the second stage of labor, twin pregnancy, preterm birth (OR 2.72, 95%CI 1.87–3.95) and preeclampsia (OR 3.24, 95%CI 1.47–7.14). Conclusion Our findings demonstrated the high mortality rate in patients who had relaparotomy after CS. Interpretation of the results should be with caution due to GRADE evidence level. During a time when there is an imbalance in medical resources in different countries, interventions to reduce CS rate, good prenatal care and intensified post-operative management are important. Trial registration PROSPEROCRD42021265325.